Correlation Between Testosterone Level With HBA1C Level As Glycemic Control Marker Among Type 2 Diabetes Mellitus Patient - Harahap, Raja Iqbal Mulya; Tristina, Nina; Nurhayati, Imas; Rachmayati, Sylvia (Medica Hospitalia : Journal of Clinical Medicine, 2023)
BACKGROUND: Type 2 Diabetes Mellitus could cause various complications due to formation of advanced glycation end products (AGEs).  The AGEs could destroy many organs into cellular level, one of them is testis, then causing testosterone production deficiency, and hypogonadism. Meanwhile, the AGEs formation in vivo will depend on on mean glucose level in T2DM patient. HbA1C is one of the most common parameter used to asses glycemic control among T2DM patient. OBJECTIVE: This research was conducted to find out the correlation between serum total testosterone with HbA1C level among T2DM patient METHOD:Research subject was collected from Outpatient Polyclinic of Internal Medicine Departement Hasan Sadikin Hospital. HbA1C examination was conducted with turbidimetry method, meanwhile total testosterone level was performed with ELISA method. The examination of research parameter was done at Clinical Laboratory Installation of Hasan Sadikin Bandung   RESULT: During sample collection periode, 70 patients was collected and fulfilled the inclusion criteria, 18 of 70 subjects has low testosteron level with Mean (SD): 424, 48 (204,82) ng/mL. Correlationntesting between the variables showed r = -0,619 , and p-value <0.001, which means strong and significant correlation between total testosterone and HbA1C among T2DM patient.   CONCLUSION: There was strong and significant correlation between total testosterone with HbA1C level among T2DM patients, further research could be conducted with prospective cohort method or using free testosterone examination.